Analysis of the Influence of Work Discipline and Motivation Employee Performance in PT. Pembangunan Perumahan (PP) Properti Tbk. Pasar Rebo – East Jakarta - I Made Aryata; Cornelia Dumarya Manik; Rudy Bodewyn Mangasa Tua (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The purpose of this research is to determine the influence of discipline and motivation employee performance in PT. PP Properti Tbk. This research method uses quantitative descriptive research methods. The sample used in this research is a random sample, namely using a portion of the population of 86 respondents as a sample. The research results show that simultaneously there is a significant influence of discipline and motivation on the performance of PT. PP Properti Tbk employees. Based on the partial test, it is known that there is a significant influence between discipline on the performance of PT. PP Properti Tbk employees, while motivation has a significant influence on the performance of PT. PP Properti Tbk employees.